Equalizing or Disequalizing Lifetime Earnings Differentials? Earnings Mobility in the EU: 1994-2001 - Denisa Maria Sologon; Cathal O'Donoghue (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Do EU citizens have an increased opportunity to improve their position in the distribution of lifetime earnings? To what extent does earnings mobility work to equalize/disequalize longerterm earnings relative to cross-sectional inequality and how does it differ across the EU? Our basic assumption is that mobility measured over a horizon of 8 years is a good proxy for lifetime mobility. We used the Shorrocks (1978) and the Fields (2008) index. Moreover, we explored the impact of differentials attrition on the two indices. The Fields index is affected to a larger extent by differential attrition than the Shorrocks index, but the overall conclusions are not altered. Based on the Shorrocks (1978) index men across EU have an increasing mobility in the distribution of lifetime earnings as they advance in their career. Based on the Fields index (2008) the equalizing impact of mobility increases over the lifetime in all countries, except Portugal, where it turns negative for long horizons. Thus, Portugal is the only country where mobility acts as a disequalizer of lifetime differentials. The highest lifetime mobility is recorded in Denmark, followed by UK, Belgium, Greece, Ireland, Netherlands, Italy, France, Spain, Germany, and the lowest, Portugal. The highest mobility as equalizer of longer term inequality is recorded in Ireland and Denmark, followed by France and Belgium with similar values, then UK, Greece, Netherlands, Germany, Spain and Italy.
Keywords: C23; D31; J31; J60; 330; panel data; wage distribution; inequality; mobility